2022
DOI: 10.3390/foods11121678
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strobilanthes tonkinensis Lindau Addition on Black Tea Flavor Quality and Volatile Metabolite Content

Abstract: The characteristic aroma of Chinese black tea (BT) produced in summer usually lacks intensity and persistence, reducing consumer acceptance and market demand. Strobilanthes tonkinensis Lindau (STL) possesses excellent biological characteristics, making it a promising novel tea ingredient. We investigated the effects of different addition methods and concentrations for the novel additive STL on the sensory quality of BT. A 20:1500 g/g addition to rolled tea leaves was identified as the best BT with STL (BoS) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…OAV is the concentration of each volatile aroma substance analysed by GC–MS divided by the odor threshold value of the substance, with compounds with an OAV greater than 1 considered to be important odor active compounds. Odor threshold values were those reported in the literature ( Culleré et al, 2007 , Costa et al, 2016 , Hua et al, 2022 , Pino and Quijano, 2012 , Pino, 2012 , Ueno et al, 2006 , Xiao et al, 2019 , Yin et al, 2023 , Zhu and Xiao, 2018 , Zhu et al, 2018 , Zhu et al, 2018 , Zhu and Xiao, 2018 ). OC expressed the OAV of each volatile fragrance component as a relative ratio (%) to the total OAV.…”
Section: Methodsmentioning
confidence: 82%
“…OAV is the concentration of each volatile aroma substance analysed by GC–MS divided by the odor threshold value of the substance, with compounds with an OAV greater than 1 considered to be important odor active compounds. Odor threshold values were those reported in the literature ( Culleré et al, 2007 , Costa et al, 2016 , Hua et al, 2022 , Pino and Quijano, 2012 , Pino, 2012 , Ueno et al, 2006 , Xiao et al, 2019 , Yin et al, 2023 , Zhu and Xiao, 2018 , Zhu et al, 2018 , Zhu et al, 2018 , Zhu and Xiao, 2018 ). OC expressed the OAV of each volatile fragrance component as a relative ratio (%) to the total OAV.…”
Section: Methodsmentioning
confidence: 82%
“…The flavour compounds with p < 0.05 and an FC value greater than 2 were selected as differential metabolites [ 40 , 41 ]. The flavour metabolites of SJ changed markedly after fermentation, with seven significantly upregulated and two downregulated VOCs ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that this study has also identified two substances, namely 2-thiophenemethanethiol and pyrazine, 2-methoxy-3-(2-methylpropyl)-, which significantly contribute to the olfactory perception of tomato fruits. These substances are known to impart coffee and green flavors to tomatoes and have been established as the primary VOCs in sesame oil and black tea [56,57]. Currently, there is limited literature documenting the effects of these two substances on various horticultural crops, including tomatoes.…”
Section: Discussionmentioning
confidence: 99%